Balancing teacher-led and student-led learning in science: the importance of cognitive load - Dean Cairns (Large-scale Assessments in Education)
Abstract A considerable body of research on student-led learning focuses on approaches such as inquiry learning in science education. However, the effectiveness of such approaches for developing conceptual understanding is less than certain. One concern is that student-led practices can overload students’ working memory and impede their ability to learn new concepts. This study investigated how students’ science lesson learning experiences (as described by items in the PISA 2015 student background questionnaire) relate to their scientific literacy levels to address gaps in understanding optimal instructional combinations. Science lesson learning experience profiles were identified from the 2015 PISA data for Singapore, the UK, and the UAE using latent profile analysis. The profiles were classified using constructivist and objectivist frameworks, and cognitive load theory was used to explain differences in scientific literacy scores across profiles. The scientific literacy score for members of a profile was estimated for all profiles (N = 34,349). The findings of this study indicate that, across all three countries, students who experienced “strong teacher-led instruction” had higher scientific literacy scores, likely due to reduced extraneous cognitive load. The implications of these findings are discussed, and recommendations for practice for managing the cognitive burden on students when they are exposed to new knowledge are made.